Mothers With Physical Disability: Child Care Adaptations at Home - Wint, Amy J. (Am J Occup Ther, 2016)
OBJECTIVE. This study describes how women with physical disability experience caregiving for a new infant and how they adapt their home environment and care tasks. METHOD. In 2013, we conducted 2-hr telephone interviews with 22 women with significant physical disability who had delivered babies within the previous 10 yr. The semistructured, open-ended interview protocol addressed wide-ranging pregnancy-related topics. NVivo was used to sort the texts for content analysis. RESULTS. Night care, bathing, and carrying the baby were identified as the biggest challenges. Typical adaptations (with and without occupational therapy consultation) included use of a wrap for carrying the infant, furniture adaptations for mothers using wheelchairs, and assistance from caregivers. CONCLUSION. Women with physical disability can be fully capable of caring for an infant and can find ways to adapt their environment. Further research may determine the role of occupation therapy.